Medievalisms : making the past in the present - Pugh, Tison; Weisl, Angela Jane, 1963- (London : Routledge, 2013)
'From Harry Potter and Robin Hood, through to video games and jousting-themed restaurants, medieval culture continues to surround us and has retained a strong influence on literature and culture throughout the ages. This fascinating and illuminating guide is written by one of the leading contemporary scholars of Medieval literature, and explores: - The influence of medieval cultural concepts on key authors such as Shakespeare, Dante, Chaucer, George Eliot and Mark Twain - The continued appeal of medieval cultural figures such as King Arthur and Robin Hood - The influence of the medieval on disciplines such as politics, music, film, and art. Medievalisms surveys the critical field and sets the boundaries for future study, providing an essential background for literary study from the Medieval period through to the twenty-first century'--
Medievalisms: the magic of the Middle Ages -- A case study of Dante: naked icons of medievalism -- Literary medievalisms: inventing inspirations --'Medieval' literature for children and young adults: fantasies of innocence -- King Arthur's and Robin Hood's adventures in medievalism: mythic masculinities (and magical femininities) -- Movie medievalisms: five (or six) ways of looking at an anachronism -- Medievalisms in music and the arts: longing for transcendance -- Experiential medievalisms: reliving the always modern middle ages -- Political medievalisms: the darkness of the dark ages.
Includes bibliographical references (p. [158]-169) and index.
Keywords: Medievalism; Medievalism -- Social aspects; Medievalism -- Political aspects; Popular culture; Commercial products -- Social aspects; Middle Ages in art; Middle Ages in literature; Middle Ages in motion pictures